Studi Tentang Syirkah Di Indonesia - Nurdiana Sari (MKKS SMA, MKKS SMP se-Kota Metro, Persatuan Sarjana Pendidikan Islam Wilayah Provinsi Lampung, dan CV.IQRO Penerbitan, 2021)
Syirkah or partnership is a form of cooperation between two or more parties to run a certain business, where there is a distribution of profits and losses based on an agreement that has been agreed upon by the parties concerned. Syirkah is divided into two types, namely syirkah amlak and syirkah uqud. Where syirkah amlak is divided into two forms, namely syirkah amlak ikhtiyar and syirkah amlak ijbar. The application of syirkah itself has progressed along with the development of the times. These applications can be found in the banking sector such as project financing and venture capital. Obstacles in the cooperation between the Bank and the customer do not rule out the possibility. Then the alternative that can be used to resolve obstacles or disputes is through deliberation, banking mediation, through arbitration bodies, through courts within the scope of general courts.